INFLUENCE BETWEEN LEARNING MOTIVATION AND STUDENTS' ANXIETY LEVEL ON MATHEMATICS LEARNING OUTCOMES OF VIII GRADE JUNIOR HIGH SCHOOL STUDENTS IN KALASAN SUBDISTRICT SLEMAN - Nanang iman Mochammad; Suparman Suparman (Universitas Ahmad Dahlan, 2017)
Students’ motivation in Mathematics that is considered low and students’ anxiety level are expected to influence the students’ learning outcome. This research aims to discover whether there are effects or not towards the Mathematics’ learning outcome between the high-motivated students in studying or the low ones and high anxiety level or low towards the students of the 8th grade of the whole junior high schools in Kalasan sub-district, Sleman, Academic Year 2014/2015. The population in this research involves all students of the 8th grade in Kalasan sub-district, Sleman, Academic Year 2014/2015 consisting of 20 classes whose students are 637. Samples in all schools were taken by using the Random Sampling technique towards classes in every school. The result is 3 classes, SMPN 1 Kalasan 8th C grade, SMPN 2 Kalasan 8th D grade, and SMPN 4 Kalasan 8th B grade as the experiment class whose students are 97. The collecting method used was a questionnaire for motivation and students’ anxiety level, and also the students’ learning outcome test method in Mathematics. The data analysis used two-way variance 2 x 2 with different cells and post ANOVA. The result of this research shows (1) The existence of study motivation’s significant effect towards the Mathematics’ learning outcome of students of SMPN 8th grade for the whole Kalasan sub-district, Sleman, Academic Year 2014/2015 of Even Semester obtained tcount > ttable = 9,48967 > 1,661 at significance level of 5%. (2) The existence of significant influence of students’ anxiety level towards the Mathematics’ learning outcome of the students in SMPN 8th grade in all Kalasan sub-district, Sleman, Academic Year 2015/2015, Even Semester obtained tcount > ttable is -10,25663 < 1, 661 at significance level of 5%. (3) The absence of mutual influence between learning motivation and students’ anxiety level on the Math’s learning outcome of the students in SMPN 8th grade in all Kalasan sub-district, Sleman, Academic Year 2015/2015, Even Semester obtained fcount < ftable is 0,91 < 3,956 at significance of level 5%.